2021
DOI: 10.1111/his.14319
|View full text |Cite
|
Sign up to set email alerts
|

Tumour budding and CD8+ T cells: ‘attackers’ and ‘defenders’ in rectal cancer with and without neoadjuvant chemoradiotherapy

Abstract: Aim Tumour budding (‘attacker’) and CD8+ T cells (‘defender’) are recognised as important parameters for risk stratification in colon cancers and, combined, may have an even stronger clinical impact. Here, we determine the value of tumour budding and CD8+ in rectal cancer patients treated with/without neoadjuvant therapy. Methods and results Using digital scans of all tumour slides/case, we analysed CD8+ T cell counts in two patient cohorts: 45 neoadjuvantly treated and 47 primarily surgically treated (totalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…5 A growing number of studies, however, suggest that TB may retain prognostic significance in the postneoadjuvant setting. [30][31][32] We found TB, PDC, and CS to all be significantly associated with RFS, DSS, and OS in the neoadjuvant treated group, further supporting the prognostic utility of these features in this setting.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…5 A growing number of studies, however, suggest that TB may retain prognostic significance in the postneoadjuvant setting. [30][31][32] We found TB, PDC, and CS to all be significantly associated with RFS, DSS, and OS in the neoadjuvant treated group, further supporting the prognostic utility of these features in this setting.…”
Section: Discussionsupporting
confidence: 61%
“…At present, most guidelines do not recommend evaluating TB postneoadjuvant therapy owing to insufficient data supporting its prognostic significance in this setting and concerns regarding the distinction of true TB from treatment effect 5. A growing number of studies, however, suggest that TB may retain prognostic significance in the postneoadjuvant setting 30–32. We found TB, PDC, and CS to all be significantly associated with RFS, DSS, and OS in the neoadjuvant treated group, further supporting the prognostic utility of these features in this setting.…”
Section: Discussionmentioning
confidence: 61%
“…TB and TIL comprise an “attacker‐defender” model, considering that the tumor and tumor microenvironment have been used in other tumors 15 . TB and TIL have been used in combination to predict prognosis of CRC patients with surgery or without adjuvant therapy 4,15 . TIL has been reported to be closely associated with the biological characteristics of ESCC 16 .…”
Section: Discussionmentioning
confidence: 99%
“…TB and tumor-infiltrating lymphocyte (TIL) have been regarded as an "attacker-defender" model in several tumors. 15 Previous studies have found that ESCC with low TIL exhibits aggressive clinical behavior and is associated with a poor prognosis. 16 In addition, it modifies the effectiveness of TB alone in providing an indication for the prognosis of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The well-established role of CD3+ and CD8+ cells in colorectal cancer (i.e., the immunoscore ( 18 )) has paved the road to investigate the impact of other immune cell subsets. CD11c+ (dendritic cells (DCs)) ( 19 , 20 ), CD20+ (B cells) ( 21 , 22 ), CD3+CD8-FOXP3-(T-helper cells) ( 10 ), CD3+FOXP3+[T-regulatory cells (T-regs)]] ( 23 , 24 ) and CD3+CD8+[cytotoxic T cells (T-cyt)] cells ( 25 , 26 ) have been some of the major targets of immune-profiling in recent years. In newly diagnosed rectal cancers, several studies have elegantly shown an increased presence of T-helper and cytotoxic T cells prior to RCT correlates with better response ( 27 , 28 ) and better recurrence-free survival ( 29 ).…”
Section: Introductionmentioning
confidence: 99%